2023
DOI: 10.3390/foods12061233
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Mexican Food: Phenolic Content and Public Health Relationship

Abstract: Phenolic compounds have a positive effect on obesity, diabetes, and cardiovascular diseases because of their antioxidant and anti-inflammatory capacity. The prevalence of these diseases has increased in the last years in the Mexican population. Therefore, the Mexican diet must be assessed as provider of phenolic compounds. To assess this, a survey of phenolic compound intake was validated and applicated to 973 adults (798 females) between 18 and 79 years old. We compared the phenolic compound intake of 324 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Meanwhile, another study identified chlorogenic, caffeoylquinic, and vanillic acids in these seeds [15]. Hydroxycinnamic acid and its intermediate derivative products such as caffeic acid, p-coumaric acid, chlorogenic acid, curcumin, and hydroxycinnamic acids are abundant in fruits, vegetables, cereals, and the seeds of several fruits [28,29]. Interestingly, there is evidence that most of the hydroxycinnamic acid derivatives can act against lipid deposition and increase hepatic lipid metabolism [30].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, another study identified chlorogenic, caffeoylquinic, and vanillic acids in these seeds [15]. Hydroxycinnamic acid and its intermediate derivative products such as caffeic acid, p-coumaric acid, chlorogenic acid, curcumin, and hydroxycinnamic acids are abundant in fruits, vegetables, cereals, and the seeds of several fruits [28,29]. Interestingly, there is evidence that most of the hydroxycinnamic acid derivatives can act against lipid deposition and increase hepatic lipid metabolism [30].…”
Section: Discussionmentioning
confidence: 99%
“…These are precious resources that were a long time in the making [33]. Phenolic compounds such as rice, beans, enchiladas, tomatoes, lettuce, and corn are found in many traditional Mexican meals and have a positive effect on health conditions [34]. Without awareness of the positive health implications of traditional food patterns, their availability will rapidly reduce and limit access to healthy food.…”
Section: Loss Of Food Heritagementioning
confidence: 99%
“…Plants synthesize phenolic compounds (PCs) to function as a chemical defense against predators, as protection against ultraviolet light, as pollinator attractants, and as participants in reproduction as well as in plant–plant interference [ 4 , 5 ]. On the other hand, in humans, they continue to be useful in the fields of health and nutrition due to the health benefits of their dietary intake, mainly protection against chronic diseases, inflammatory states, and dysfunctional mechanisms associated with oxidative stress [ 1 , 4 , 6 , 7 , 8 , 9 ]. As an example, a lower risk of suffering a myocardial infarction, diabetes, and a cerebral vascular accident, as well as improvements in blood flow and blood pressure, among others, have been associated with the consumption of the flavan-3-ols found in cocoa, while resveratrol and quercetin improve cardiometabolic health.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this evidence, some researchers have worked to promote the consumption of diets rich in these compounds [ 4 , 9 ]. Others have highlighted the importance of generating clear and regulated alternatives in the food industry through their incorporation into foodstuffs, nutraceutical formulations, and the production of dietary supplements.…”
Section: Introductionmentioning
confidence: 99%